A new species and a new record of Curcuma subgen. Curcuma (Zingiberaceae) from Northern Thailand - Surapon Saensouk; Thawatphong Boonma; Piyaporn Saensouk (Society for Indonesian Biodiversity, 2021)
Abstract. Saensouk S, Boonma T, Saensouk P. 2021. A new species and a new record of Curcuma subgen. Curcuma (Zingiberaceae) from Northern Thailand. Biodiversitas 22: 3617-3626. Recent fieldwork to study the species diversity of the Zingiberaceae family in Thailand and preparing a revision of the Curcuma genus for the Flora of Thailand, an undescribed species of Curcuma uses as traditional medicinal for more than two decades well known in the Thai vernacular name “Rang-Jued” was found, this vernacular name is also used to call the other two medicinal plants belonging to different families which are Thunbergia laurifolia Lindl. (Acanthaceae), and Crotalaria spectabilis Roth (Fabaceae), thus some villagers are named Curcuma rangjued as “Rang-Jued-Khamin” to communicate specifically identify species in order to use correct species for each utilization. While Thunbergia laurifolia was called